2016
DOI: 10.1093/europace/euv422
|View full text |Cite
|
Sign up to set email alerts
|

Circulating intermediate CD14++CD16+monocytes are increased in patients with atrial fibrillation and reflect the functional remodelling of the left atrium

Abstract: Intermediate CD14++CD16+monocytes might be closely related to the pathogenesis of AF and reflect functional remodelling of the left atrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 20 publications
3
31
2
1
Order By: Relevance
“…One of the important limitations of our study was using an automatically counted monocyte numbers rather than the proportion of monocyte subsets. Thus, the study by Suzuki et al 1 may support and confirm our previous findings when the ratio of circulating intermediate CD14þþCD16þ monocytes to HDL-C levels has been calculated and analysed. Because MHR combines the two detrimental processes like inflammation and oxidative stress, it could be used as a novel marker for prediction of the severity of atrial remodelling.…”
Section: Letters To the Editorsupporting
confidence: 88%
See 3 more Smart Citations
“…One of the important limitations of our study was using an automatically counted monocyte numbers rather than the proportion of monocyte subsets. Thus, the study by Suzuki et al 1 may support and confirm our previous findings when the ratio of circulating intermediate CD14þþCD16þ monocytes to HDL-C levels has been calculated and analysed. Because MHR combines the two detrimental processes like inflammation and oxidative stress, it could be used as a novel marker for prediction of the severity of atrial remodelling.…”
Section: Letters To the Editorsupporting
confidence: 88%
“…We would like to thank Dr Albert, Founder and Chief Medical Officer of AliveCor, for his interpretation of our study results to the readership in the light of different software versions. 1 As one may have noted in the article, 'despite' the findings of our study, our conclusions were positive about using AliveCor (as well as MyDiagnostick) in a hospital screening setting. 2 Those conclusions only get stronger with the clarifications of Dr Albert.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…+ monocytes than the controls, 23) although several papers have recently revealed that the cell counts of intermediate CD14 ++…”
Section: Article P64mentioning
confidence: 93%